Who wants to be a scientist? : choosing science as a career - Rothwell, Nancy (Cambridge, U.K. ; New York : Cambridge University Press, 2002)
Scientific research is about discovering new things and applying them to improvements in life style for people and animals. Careers in science are now very demanding, requiring much more than a keen scientific mind and practical ability. This book offers practical advice on how to choose science as a career.
Introduction -- Starting out in research -- Getting down to research -- Scientific ethics and conduct -- Publish or perish? -- Communication and getting known -- Moving up -- Responsibilities -- Funding research -- Who owns science? -- Science and the public -- Power, pressure and politics -- Social aspects of science -- So who does want to be a scientist?
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Science -- Vocational guidance; Sciences -- Orientation professionnelle; SCIENCE -- General; Science -- Vocational guidance; Electronic books; Handbooks and manuals